Knowledge, barriers and uptake of influenza vaccine among non-health college students at Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia - Malak M. Alhawsawi; Amjad A. Alghamdi; Balqees M. Alzayed; Hessa M. Binmugren; Raghad A. Alshehri; Howeida H. Abusalih (SAGE Publishing, 2020)
Background: Viral influenza, one of the global public health problems is specifically important in Saudi Arabia due to high susceptibility of transmission in hajj and umrah seasons (Islamic pilgrimage to the Mecca), as it has the ability to spread widely to a large proportion, in addition the disease has a higher rate of complications that might lead to death. Vaccination is an important strategy in prevention of viral influenza. Design and methods: The study aimed to describe the association between uptake of influenza vaccine with knowledge as well as identify the barriers that prevent vaccination among Princess Nourah Bint Abdulrahman University (PNU) non-health colleges students. A descriptive cross-sectional study design was undertaken, including 385 students from non-health colleges using a convenience sampling technique. Data was collected using an Arabic self-administered online questionnaire Analysis done by JMP program. IRB approval as well as informed consent were taken. Results: The uptake of the influenza vaccine was 15.3% in the current year and 56.8% in the previous years. No significant association was found between knowledge, and uptake of the vaccine. For the unvaccinated students, the most common encounter barriers stated by study population were concerns regarding the vaccine effectiveness, reduction of immunity the uncertainty of complete protection in a percentage of 12.0% for all. Conclusions: Although the level of vaccine uptake is low for this year, it is not associated with knowledge. There were some barriers that need to be tackled by health education programs.